Relationship Knowledge And Attitude Of Pregnant Women Aboutanemia Incidence At The Mamboro Community Health Center - Nurhaeda Nurhaeda; Kasmiati Kasmiati; Aisyah Aisyah; Fadly Fadly (International Journal of Medicine and Health, 2022)
Background. Anemia during pregnancy is still a major problem in the world today because it is one of the causes of maternal death or also known as "Potentional Danger To Mother And Child". The high incidence of anemia in pregnant women is multifactorial, from a pure deficiency of iron, folate, B12, the level of knowledge and attitudes of pregnant women about the incidence of anemia. Objective. To determine the relationship between the knowledge and attitudes of pregnant women towards the incidence of anemia at the Mamboro Health Center Research methods. The type of research used is quantitative research with a Cross Sectional Study approach. The sample is 20 people with the sampling technique using the feeder formula. Research result. The results of the study with 20 respondents having good knowledge were 1 respondent (5.0%) with anemia, 8 respondents (40.0%) good knowledge not anemia and as many as 11 respondents (55.0%) lacking knowledge with anemia, Based on data analysis with Fisher's test Relationship between knowledge and The incidence of Anemia obtained p value = .000 <0.05 and the relationship between Attitude and Anemia Incidence with Fisher's test obtained p value = 0.004 <0.05 with the results of a positive attitude study of 1 respondent (5.0%) with anemia, 6 respondents (30.0%) attitude positive without anemia. And as many as 11 respondents (55.0%) have a negative attitude with anemia. 2 respondents (10.0%) had a negative attitude with no anemia. Conclusion. there is a relationship between knowledge and the incidence of anemia and there is a relationship between the attitudes of pregnant women and the incidence of anemia.